Disappointment aversion and social comparisons in a real-effort competition - Simon Gächter; Lingbo Huang; Martin Sefton (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2017)
This paper investigates the contribution of social comparison effects to the disappointment aversion previously identified in a two-person real-effort competition (Gill and Prowse, 2012). "Social" and "asocial" versions of the Gill and Prowse experiment are compared, where the latter treatment involves a competition against Nature and removes the scope for social comparisons. If disappointment aversion simply reflects an asymmetric evaluation of losses and gains it is expected to survive in the asocial treatment, whereas treatment differences are expected if losing to or winning against another person affects the evaluation of losses/gains. The main result is that behaviour is very similar in social and asocial treatments, suggesting that social comparisons have little impact in this setting. Two other unexpected findings of the paper are that prize effects are much weaker than those identified in Gill and Prowse (2012) and, in neither treatment is there evidence of disappointment aversion.
Keywords: C91; D12; D81; D84; 330; real effort competition; social comparison effects; disappointment aversion; reference-dependent preferences